Early cardiac injury in acute respiratory distress syndrome: comparison of two experimental models - Mikolka, Pavol; Košútová, P; Bálentová, Soňa; Čierny, Daniel; Kopincová, Jana; Kolomazník, Maroš; Adamkov, Marian; Čalkovská, Andrea; Mokrá, Daniela (Physiological research, 2020)
Acute respiratory distress syndrome (ARDS) is characterized by diffuse lung damage, inflammation, oedema formation, and surfactant dysfunction leading to hypoxemia. Severe ARDS can accelerate the injury of other organs, worsening the patient ́s status. There is an evidence that the lung tissue injury affects the right heart function causing cor pulmonale. However, heart tissue changes associated with ARDS are still poorly known. Therefore, this study evaluated oxidative and inflammatory modifications of the heart tissue in two experimental models of ARDS induced in New Zealand rabbits by intratracheal instillation of neonatal meconium (100 mg/kg) or by repetitive lung lavages with saline (30 ml/kg). Since induction of the respiratory insufficiency, all animals were oxygen-ventilated for next 5 h. Total and differential counts of leukocytes were measured in the arterial blood, markers of myocardial injury [(troponin, creatine kinase - myocardial band (CK-MB), lactate dehydrogenase (LD)] in the plasma, and markers of inflammation [tumour necrosis factor (TNF)alpha, interleukin (IL)-6], cardiovascular risk [galectin-3 (Gal-3)], oxidative changes [thiobarbituric acid reactive substances (TBARS), 3-nitrotyrosine (3NT)], and vascular damage [receptor for advanced glycation end products (RAGE)] in the heart tissue. Apoptosis of heart cells was investigated immunohistochemically. In both ARDS models, counts of total leukocytes and neutrophils in the blood, markers of myocardial injury, inflammation, oxidative and vascular damage in the plasma and heart tissue, and heart cell apoptosis increased compared to controls. This study indicates that changes associated with ARDS may contribute to early heart damage what can potentially deteriorate the cardiac function and contribute to its failure.
Keywords: Lung Injury; Animals; poškození plic; Rabbits; apoptóza; zánět; Female; Heart Injuries; biologické markery; oxidační stres; syndrom dechové tísně; Biomarkers; Apoptosis; ženské pohlaví; Oxidative Stress; syndrom aspirace mekonia; Meconium Aspiration Syndrome; Inflammation; Male; modely nemocí na zvířatech; Disease Models, Animal; poranění srdce; Respiratory Distress Syndrome; králíci; zvířata; mužské pohlaví